A cross-sectional investigation of parenting style and friendship as mediators of the relation between social class and mental health in a university community. Issue 1 (December 2015) - Rubin, Mark; Kelly, Benjamin
Abstract Introduction This study tested a novel explanation for the positive relation between social class and mental health among university students. Students with a higher social class were expected to have experienced more authoritative and less authoritarian parenting styles; these parenting styles were expected to lead to greater friendship and social integration at university; and greater friendship and integration were expected to lead to better mental health. Method To test this model, the researchers asked 397 Australian undergraduate students to complete an online survey. The research used a cross-sectional correlational design, and the data was analysed using bootstrapped multiple serial mediation tests. Results Consistent with predictions, parenting style, general friendship and support, and social integration at university mediated the relation between social class and mental health. Conclusions The present results suggest that working-class parenting styles may inhibit the development of socially-supportive friendships that protect against mental health problems. The potential effectiveness of interventions based on (a) social integration and (b) parenting style is discussed. Future research in this area should employ a longitudinal research design in order to arrive at clearer causal conclusions about the relations between social class, parenting styles, friendship, social integration, and mental health.